DESCRIPTION OF THE PROCESSES OF ORGANIZING THE ACTIVITIES OF THE STANDARDIZATION DEPARTMENT IN THE ORGANIZATION - Fattoev Firuz Farhod ogli (American Journals Publishing, 2024)
The organization's standardization system, standardization processes, management of the standardization service using theMarkov chain, and the procedure for developing standards within the organization.
Keywords: Standard, standardization, Markov chain, standardization service, experts, processes.